Glass component

By forming a specific concave and convex structure on the surface of the glass component, the problem of easy wear of the coating in the prior art is solved, and high water repellency that does not rely on the coating is achieved, and it is suitable for various outdoor camera components.

CN119866320APending Publication Date: 2025-04-22NIPPON ELECTRIC GLASS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380065811.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-31
Filing Date
2023-10-26
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, when improving the water removability of glass components, the coating is prone to wear or peeling due to friction, and it is difficult to maintain high water removability for a long time.

Method used

By forming an uneven structure on the surface of the glass component, the number of convex parts in the 96 μm×72 μm area is ensured to be more than 10 or less than 250, and the arithmetic average height in the 5 μm×5 μm micro area is more than 1.0 nm or less than 50.0 nm to improve water removability.

Benefits of technology

It achieves high water repellency without relying on coating, and can maintain excellent water repellency performance for a long time. It is suitable for on-board cameras and other camera lens components and cover components for outdoor use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866320A_ABST
    Figure CN119866320A_ABST
Patent Text Reader

Abstract

Provided is a glass member having excellent water repellency. A glass member (1) having irregularities in at least a portion of a surface (1a), the number of protrusions having a height of 50 nm or more from a reference surface being 10-250 when the average surface of the irregularities is defined as the reference surface in a 96 [mu] m * 72 [mu] m region of the surface (1a) having irregularities, and the number of protrusions having a height of 50 nm or more from the reference surface being 10-250 when the average surface of the irregularities is defined as the reference surface in a 5 [mu] m * 5 [mu] m minute region of the surface (1a) having irregularities. When the cutoff value of the high-pass filter [lambda] c is 2.5 [mu] m, the arithmetic average height Sa is 1.0 nm or more and 50.0 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a glass component with water repellency. Background Art

[0002] In cameras used outdoors, such as car cameras and surveillance cameras, it is necessary to prevent water droplets from adhering to the camera surface so that clear images can be obtained even on rainy days. Therefore, glass components with high water repellency are required as lens components and cover components of cameras used outdoors. As such, the demand for glass components with high water repellency has been increasing in recent years.

[0003] The following patent document 1 discloses a water-repellent cleaning structure for a front lens of a vehicle lamp, characterized in that a cleaning liquid spray nozzle is arranged in front of the front lens, and a fluorine-based or silicone-based resin coating is applied to the surface of the front lens. The cleaning liquid spray nozzle is formed with a spray outlet for pressurizing and spraying cleaning water toward the front of the front lens.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 6-330363 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] However, when a coating composed of an organic fluorine compound or the like is formed on the surface of a glass member as in Patent Document 1, the coating is often extremely thin and may be worn or peeled off due to friction or the like. Therefore, it may be difficult to maintain high water repellency for a long time.

[0009] An object of the present invention is to provide a glass component having excellent water repellency.

[0010] Technical solutions for solving technical problems

[0011] Various aspects of the glass component that solve the above-mentioned problems will be described.

[0012] The glass component involved in mode 1 of the present invention is characterized in that the glass component has unevenness on at least a portion of the surface, and in an area of ​​96μm×72μm on the surface having the unevenness, when the average plane of the unevenness is used as a reference plane, the number of convex parts having a height of 50nm or more from the reference plane is greater than 10 and less than 250, and in a small area of ​​5μm×5μm on the surface having the unevenness, when the cutoff value of the high-pass filter λc is set to 2.5μm, the arithmetic mean height Sa is greater than 1.0nm and less than 50.0nm.

[0013] The glass component according to the second aspect of the present invention is characterized in that the glass component has concavities and convexities on at least a portion of the surface, and in a region of 96 μm×72 μm on the surface having the concavities and convexities, when an average plane of the concavities and convexities is taken as a reference plane, a value (S / N) obtained by dividing an area (S) having a height less than 50 nm from the reference plane by the number (N) of convex portions having a height of 50 nm or more from the reference plane is 20.0 μm. 2 Above 500.0μm 2 Next, in a micro region of 5 μm×5 μm on the surface having the above-mentioned irregularities, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the arithmetic mean height Sa is not less than 1.0 nm and not more than 50.0 nm.

[0014] In the glass member of aspect 3, in aspect 1 or aspect 2, the average value of the height of the apex of the convex portion from the reference plane in a 96 μm×72 μm region of the surface having the concavities and convexities is preferably 0.10 μm to 5.00 μm.

[0015] In the glass member of aspect 4, in any of aspects 1 to 3, when the cutoff value of the high-pass filter λc is set to 2.5 μm in a micro region of 5 μm×5 μm on the surface having the irregularities, the skewness Ssk is preferably -0.10 or less.

[0016] In the glass member of aspect 5, in any of aspects 1 to 4, it is preferred that the contact angle between the surface having the projections and recesses of the glass member and water is 90° or more.

[0017] The glass member of aspect 6, in any of aspects 1 to 5, may include a glass member body and a water-repellent film provided on a main surface of the glass member body.

[0018] The glass member of aspect 7, in any of aspects 1 to 5, may include a glass member body and an optically functional film provided on a main surface of the glass member body.

[0019] In the glass member of aspect 8, in aspect 7, the optical functional film is preferably an antireflection film or a reflection film.

[0020] Effects of the Invention

[0021] According to the present invention, a glass component having excellent water repellency can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic cross-sectional view showing the glass component according to the first embodiment of the present invention.

[0023] Figure 2This is a diagram showing a roughness curve of a relatively small region on the first main surface of the glass member according to the first embodiment of the present invention.

[0024] Figure 3 This is a diagram showing a roughness curve of a relatively large area on the first main surface of the glass member according to the first embodiment of the present invention.

[0025] Figure 4 It is a schematic cross-sectional view showing a glass component according to a second embodiment of the present invention.

[0026] Figure 5 This is a photograph of a glass member obtained in Example 2 with a water drop placed on its surface.

[0027] Figure 6 This is a photograph of a glass member obtained in Comparative Example 1 when a water droplet is placed on the surface of the glass member.

[0028] Figure 7 This is a photograph of a glass member obtained in Comparative Example 2 when a water droplet is placed on the surface of the glass member. DETAILED DESCRIPTION

[0029] Hereinafter, preferred embodiments will be described. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments. In addition, in each of the drawings, components having substantially the same function are sometimes referred to by the same reference numerals.

[0030] (First Embodiment)

[0031] Figure 1 It is a schematic cross-sectional view showing the glass component according to the first embodiment of the present invention.

[0032] The glass member 1 has a rectangular plate shape. However, the shape of the glass member 1 is not particularly limited, and may be a plate shape having a circular or polygonal outline, a shape obtained by bending the entire plate-shaped member, a spherical lens shape, an aspherical lens shape, or the like.

[0033] The material of the glass member 1 is not particularly limited, and examples thereof include quartz glass, soda-lime glass, alkali-free glass, aluminosilicate glass, borosilicate glass, phosphate glass, fluoride glass, chalcogenide glass, etc. These materials may be used alone or in combination of two or more.

[0034] The thickness of the glass member 1 is not particularly limited, and may be, for example, 50 μm or more and 100 mm or less.

[0035] The glass member 1 has a first main surface 1a and a second main surface 1b facing each other. The first main surface 1a and the second main surface 1b are surfaces of the glass member 1. In the present embodiment, the first main surface 1a of the glass member 1 has irregularities formed all over.

[0036] In addition, in the present invention, it is sufficient that the concavoconvex is provided on at least a portion of the first main surface 1a of the glass member 1. The above-mentioned concavoconvex is preferably provided on 1% or more of the first main surface 1a of the glass member 1, more preferably provided on 30% or more, and further preferably provided on 50% or more. However, as in the present embodiment, the above-mentioned concavoconvex may be provided on the entire surface of the first main surface 1a of the glass member 1. In addition, the above-mentioned concavoconvex may be provided on the second main surface 1b of the glass member 1, or may be provided on both the first main surface 1a and the second main surface 1b.

[0037] In the first invention of the present invention, in a region of 96 μm×72 μm on the first main surface 1a (hereinafter also referred to as the surface) having unevenness, when the average surface of the unevenness is taken as the reference surface, the number (N) of convex portions having a height of 50 nm or more from the reference surface is 10 or more and 250 or less. In addition, in the first invention, in a micro region of 5 μm×5 μm on the first main surface 1a (surface) having unevenness, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the arithmetic mean height Sa is 1.0 nm or more and 50.0 nm or less.

[0038] In the second invention of the present invention, in the area of ​​96 μm×72 μm of the first main surface 1a (hereinafter also referred to as the surface) having unevenness, when the average surface of the unevenness is taken as the reference surface, the value (S / N) obtained by dividing the area (S) of the height less than 50 nm from the reference surface by the number (N) of the convex portions having a height of 50 nm or more from the reference surface is 20.0 μm. 2 Above 500.0μm 2 Furthermore, in a micro region of 5 μm×5 μm on the first main surface 1 a (surface) having irregularities, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the arithmetic mean height Sa is 1.0 nm to 50.0 nm.

[0039] In addition, when obtaining the number (N) of convex portions with a height of 50nm or more from the reference plane, the surface roughness is measured based on ISO 25178, and the average plane of the average height of the Z direction of the concave and convex is used as the reference plane. Then, the height of 50nm from the reference plane is used as a threshold for binarization, and the independent area of ​​the height above the threshold is used as one convex portion. The number (N) of the above-mentioned convex portions can be obtained according to the number of independent areas of height above the threshold. In addition, sometimes the number (N) of convex portions with a height of 50nm or more from the reference plane is also referred to as the number (N) of convex portions.

[0040] In addition, the area (S) less than the height of 50nm from the reference plane refers to the area outside the area of ​​the convex portion, which can be obtained as follows, according to the total of the projected area of ​​the region of the height above the threshold value when the height of 50nm from the reference plane is binarized as the threshold value, the area of ​​the convex portion is obtained, and then the area of ​​the convex portion is subtracted from the total area, thereby obtaining. In addition, the area (S) less than the height of 50nm from the reference plane is sometimes referred to as the projected area (S) outside the convex portion. And, sometimes the value (S / N) obtained by dividing the projected area (S) outside the convex portion by the number (N) of the convex portion is referred to as value (S / N).

[0041] In addition, the "arithmetic mean height Sa" is a parameter specified in ISO 25178, which is a parameter obtained by extending the measured cross-sectional curve representing the cross-sectional shape of the concave and convex to the surface. Specifically, the arithmetic mean height Sa can be obtained by averaging the absolute values ​​of the heights Zn of the concave and convex in a specified three-dimensional region (Sa = (Σ|Zn|) / n). In the present invention, the measurement is performed in an area of ​​5μm×5μm, and the cutoff value of the high-pass filter λc is set to 2.5μm to obtain the arithmetic mean height Sa.

[0042] Hereinafter, the first invention and the second invention may be collectively referred to as the present invention. The first invention and the second invention may be implemented individually or in combination.

[0043] The glass member 1 of this embodiment has the above-mentioned structure of the present invention, and therefore has excellent water repellency even without forming a water repellent film on the surface. In addition, in the present invention, a water repellent film may not be formed, and a water repellent film may be provided as in the second embodiment described later.

[0044] It is known that when a solid surface has asperities, the tendency of the solid surface to be wetted by water greatly differs depending on whether the solid is hydrophilic or water-repellent.

[0045] Specifically, in the case of a hydrophilic solid, the hydrophilicity is further improved by forming irregularities on the solid surface, while in the case of a water-repellent solid, the water-repellency is further improved by forming irregularities on the solid surface. This can be explained by the Wenzel model.

[0046] At this time, since the surface of the glass member is hydrophilic, the hydrophilicity is further improved when the irregularities are formed on the surface.

[0047] In view of this, the inventors of the present invention focused on both the roughness curve of a relatively small area of ​​the first main surface 1a (surface) of the glass member 1 and the roughness curve of a relatively large area of ​​the first main surface 1a (surface) of the glass member 1. The roughness curve of a relatively small area of ​​the surface of the glass member 1 is expressed as Figure 2 In addition, the roughness curve of a relatively large area of ​​the surface of the glass component 1 is expressed as Figure 3 The roughness curve shown. Figure 2 and Figure 3 The roughness curve is a schematic roughness curve shown for illustration purposes. Figure 3 The part enclosed by the dotted line A and Figure 2 The roughness curve corresponds to .

[0048] Specifically, the inventors of the present invention found that, in the first invention, by adjusting the number (N) of protrusions in a relatively large area (an area of ​​96 μm×72 μm) on the surface of the glass component 1 and the arithmetic mean height Sa of a relatively small area (an area of ​​5 μm×5 μm) on the surface of the glass component 1 within a specific range, the water repellency of the surface of the glass component 1 can be unexpectedly improved.

[0049] In addition, regarding this point, it can be considered as follows. It can be considered that by making the number of convex parts (N) on the surface of the glass member 1 greater than 10 and less than 250, and making the arithmetic mean height Sa of the surface of the glass member 1 greater than 1.0 nm and less than 50.0 nm, more air layers can be retained in the concave and convex parts of the surface of the glass member 1, and the wettability of the surface is reduced. It can be considered that as a result, the water repellency of the surface of the glass member 1 is improved.

[0050] In the first invention, the number (N) of protrusions on the surface of the glass component 1 is preferably 15 or more, more preferably 20 or more, further preferably 25 or more, further more preferably 30 or more, further more preferably 40 or more, further more preferably 50 or more, particularly preferably 100 or more, most preferably 150 or more, preferably 245 or less, more preferably 240 or less, further preferably 235 or less, particularly preferably 230 or less, and most preferably 225 or less.

[0051] When the number (N) of the convex portions on the surface of the glass component 1 is greater than the above lower limit, the concave and convex portions on the surface of the glass component 1 are less likely to be immersed in liquid, and the air layer can be more reliably maintained. Thus, the water repellency can be further improved. In addition, when the number (N) of the convex portions on the surface of the glass component 1 is less than the above upper limit, the concave and convex portions on the surface of the glass component 1 can more reliably maintain the air layer. Thus, the water repellency can be further improved.

[0052] In the first invention, in a region of 96 μm×72 μm on the surface of the glass member 1 having the unevenness, when the average surface of the unevenness is taken as the reference plane, the number (N2) of convex portions having a height of 100 nm or more from the reference plane is preferably 15 or more, more preferably 20 or more, further preferably 30 or more, and preferably 245 or less, more preferably 235 or less, further preferably 225. The number (N2) of convex portions can be obtained by the same method as the number (N) of convex portions described above, except that the height from the reference plane is set to 100 nm or more.

[0053] When the number (N2) of the convex portions on the surface of the glass component 1 is greater than the above lower limit, the concave and convex portions on the surface of the glass component 1 are less likely to be immersed in liquid, and the air layer can be more reliably maintained. Thus, the water repellency can be further improved. In addition, when the number (N2) of the convex portions on the surface of the glass component 1 is less than the above upper limit, the concave and convex portions on the surface of the glass component 1 can more reliably maintain the air layer. Thus, the water repellency can be further improved.

[0054] In addition, in the first invention, the value obtained by dividing the absolute value of the difference between the number of protrusions (N) and the number of protrusions (N2) by the number of protrusions (N) is expressed as a percentage, that is, the increase and decrease rate ((|N-N2| / N)×100) is preferably 50% or less, more preferably 25% or less, and further preferably 10% or less. The lower limit of the increase and decrease rate ((|N-N2| / N)×100) is not particularly limited and can be 0.1% or more or 1% or more.

[0055] When the increase / decrease rate ((|N-N2| / N)×100) is below the upper limit, the heights of the convex portions on the surface of the glass member 1 are more uniform, so liquid is less likely to penetrate between the convex portions, and the air layer can be more reliably maintained. Thus, the water repellency can be further improved.

[0056] In addition, the inventors of the present invention have discovered that in the second invention, by adjusting the value (S / N) of a relatively large area (an area of ​​96 μm×72 μm) on the surface of the glass component 1 and the arithmetic mean height Sa of a relatively small area (an area of ​​5 μm×5 μm) on the first main surface 1a of the glass component 1 within a specific range, the water repellency of the surface of the glass component 1 can also be unexpectedly improved.

[0057] In addition, regarding this point, it can be considered as follows. It is considered that by setting the value (S / N) of the surface of the glass member 1 to 20.0 μm 2 Above 500.0μm 2By making the arithmetic mean height Sa of the surface of the glass member 1 between 1.0 nm and 50.0 nm, more air layers can be retained in the concave and convex portions of the surface of the glass member 1, and the wettability of the surface is reduced. As a result, it is believed that the water repellency of the surface of the glass member 1 is improved.

[0058] In the second invention, the value (S / N) of the surface of the glass member 1 is preferably 21.0 μm 2 More preferably, 22.0 μm 2 More preferably, 23.0 μm 2 More preferably, 24.0 μm 2 More preferably, 25.0 μm 2 More preferably, 30.0 μm 2 More preferably, 40.0 μm 2 More preferably, 50.0 μm 2 More preferably, 70.0 μm 2 More than, particularly preferably 100.0 μm 2 More than, most preferably 150.0 μm 2 Above, preferably 400.0 μm 2 Below, more preferably 350.0 μm 2 Below, more preferably 300.0 μm 2 Below, particularly preferably 250.0 μm 2 Below, most preferably 230.0 μm 2 the following.

[0059] When the value (S / N) on the surface of the glass member 1 is equal to or greater than the lower limit, more air layers can be retained in the concave portions of the concavoconvex portions on the surface of the glass member 1. This can further improve the water repellency.

[0060] When the value (S / N) on the surface of the glass member 1 is equal to or less than the upper limit, the concave portions of the concavoconvex portions on the surface of the glass member 1 are less likely to be penetrated by liquid, and the air layer can be more reliably maintained. Thus, the water repellency can be further improved.

[0061] Therefore, by setting the above value (S / N) of the surface of the glass member 1 to be within the above range, the water repellency of the surface of the glass member 1 can be further improved.

[0062] In the present invention, the arithmetic mean height Sa of the surface of the glass component 1 is preferably greater than 2.0 nm, more preferably greater than 3.0 nm, further preferably greater than 4.0 nm, particularly preferably greater than 5.0 nm, most preferably greater than 6.0 nm, preferably less than 45.0 nm, more preferably less than 40.0 nm, further preferably less than 35.0 nm, particularly preferably less than 30.0 nm, and most preferably less than 25.0 nm.

[0063] When the arithmetic mean height Sa of the surface of the glass component 1 is above the above lower limit, the concave and convex parts of the surface of the glass component 1 can retain more air layers. Thus, the water repellency can be further improved. In addition, when the arithmetic mean height Sa of the surface of the glass component 1 is below the above upper limit, the concave and convex parts of the surface of the glass component 1 are less likely to be immersed in liquid, and the air layer can be more reliably retained. Thus, the water repellency can be further improved. In addition, when the arithmetic mean height Sa of the surface of the glass component 1 is below the above upper limit, the scattering of light caused by the concave and convex shape is less likely to occur, and the transparency of the surface of the glass component 1 is less likely to be damaged.

[0064] In the present invention, when the cutoff value of the high-pass filter λc is set to 2.5μm in an area of ​​5μm×5μm at a position lower than the above-mentioned reference plane, the arithmetic mean height SaA is preferably greater than 1.0nm, more preferably greater than 2.0nm, further preferably greater than 3.0nm, further more preferably greater than 4.0nm, particularly preferably greater than 5.0nm, most preferably greater than 6.0nm, preferably less than 50.0nm, more preferably less than 45.0nm, further preferably less than 40.0nm, further more preferably less than 35.0nm, particularly preferably less than 30.0nm, and most preferably less than 25.0nm.

[0065] The arithmetic mean height SaA can be measured in accordance with ISO 25178, similarly to the "arithmetic mean height Sa". Specifically, the arithmetic mean height SaA is as follows: Figure 3 As shown by the dotted line A, it can be obtained by measuring the arithmetic mean height of a micro area lower than the above-mentioned reference surface.

[0066] When the arithmetic mean height SaA of the surface of the glass component 1 is above the above lower limit, the concave and convex parts of the surface of the glass component 1 can retain more air layers. Thus, the water repellency can be further improved. In addition, when the arithmetic mean height SaA of the surface of the glass component 1 is below the above upper limit, the concave and convex parts of the surface of the glass component 1 are less likely to be immersed in liquid, and the air layer can be more reliably retained. Thus, the water repellency can be further improved. In addition, when the arithmetic mean height SaA of the surface of the glass component 1 is below the above upper limit, the scattering of light caused by the concave and convex shape is less likely to occur, and the transparency of the surface of the glass component 1 is less likely to be damaged.

[0067] In the present invention, in a 5 μm×5 μm region at the top of a convex portion having a height of 50 nm or more from the above-mentioned reference plane, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the arithmetic mean height SaB is preferably 1.0 nm or more, more preferably 2.0 nm or more, further preferably 3.0 nm or more, further more preferably 4.0 nm or more, particularly preferably 5.0 nm or more, and most preferably 6.0 nm or more, preferably 50.0 nm or less, more preferably 45.0 nm or less, further preferably 40.0 nm or less, further more preferably 35.0 nm or less, particularly preferably 30.0 nm or less, and most preferably 25.0 nm or less. The arithmetic mean height SaB, like the “arithmetic mean height Sa”, can be measured in accordance with ISO 25178. Specifically, the arithmetic mean height SaB is as follows: Figure 3 As shown by the dotted line B, it can be obtained by measuring the arithmetic average height of the micro area of ​​the top of the convex portion having a height of 50 nm or more from the above-mentioned reference surface.

[0068] When the arithmetic mean height SaB on the surface of the glass component 1 is above the above lower limit, the concave and convex parts on the surface of the glass component 1 can retain more air layers. Thus, the water repellency can be further improved. In addition, when the arithmetic mean height SaB on the surface of the glass component 1 is below the above upper limit, the concave and convex parts on the surface of the glass component 1 are less likely to be immersed in liquid, and the air layer can be more reliably retained. Thus, the water repellency can be further improved. In addition, when the arithmetic mean height SaB on the surface of the glass component 1 is below the above upper limit, the scattering of light caused by the concave and convex shape is less likely to occur, and the transparency of the surface of the glass component 1 is less likely to be damaged.

[0069] In the present invention, unless otherwise specified, the arithmetic mean height Sa is the height of a micro area ( Figure 3The arithmetic mean height SaA of the area shown by the dotted line A can be used, or the arithmetic mean height SaB of a tiny area at the top of a convex portion having a height of more than 50 nm from the above-mentioned reference plane can be used, or the average value of the arithmetic mean height SaA and the arithmetic mean height SaB can be used.

[0070] When measuring the arithmetic mean height SaA and the arithmetic mean height SaB, if a 5 μm×5 μm area cannot be obtained in the measurement area (for example, when the area of ​​the convex portion is less than 5 μm×5 μm), or if the measurement area includes a boundary between a convex portion and a concave portion, the measurement value is not used. In addition, when measuring the arithmetic mean height Sa, if either the arithmetic mean height SaA or the arithmetic mean height SaB cannot be measured, the measurement value of the measurable one is used.

[0071] In addition, in the present invention, when both the arithmetic mean height SaA and the arithmetic mean height SaB can be measured, the absolute value of (SaA-SaB) / Sa is preferably 0.2 or less, more preferably 0.1 or less, and further preferably 0.05 or less. The lower limit of the absolute value of (SaA-SaB) / Sa is not particularly limited, and may be 0 or more, or 0.01 or more. When the absolute value of (SaA-SaB) / Sa is below the above upper limit, uniform water repellency can be easily obtained.

[0072] In the present invention, in the area of ​​96μm×72μm on the surface of the glass component 1, the average value of the height of the vertex of the protrusion from the above-mentioned reference plane is preferably greater than 0.07μm, more preferably greater than 0.10μm, further preferably greater than 0.12μm, particularly preferably greater than 0.15μm, most preferably greater than 0.20μm, preferably less than 5.00μm, more preferably less than 4.50μm, further preferably less than 4.00μm, particularly preferably less than 3.00μm, and most preferably less than 2.50μm.

[0073] The height of the apex of the convex portion from the reference plane is the maximum height of one convex portion from the reference plane (height 0.0 μm). In addition, the average value of the height of the apex of the convex portion from the reference plane (hereinafter also referred to as the height of the apex of the convex portion) refers to the value obtained by calculating the height of the apex of the convex portion from all convex portions having a height of 50 nm or more from the reference plane in the area of ​​96 μm×72 μm on the first main surface 1a of the glass member 1, and then averaging the heights of the apex of the convex portion.

[0074] When the average value of the height of the convex vertices on the surface of the glass component 1 is greater than the above lower limit, the concave and convex concave portions on the surface of the glass component 1 are less likely to be immersed in liquid, and the air layer can be more reliably maintained. Thus, the water repellency can be further improved. In addition, when the average value of the height of the convex vertices on the surface of the glass component 1 is less than the above upper limit, the scattering of light caused by the concave and convex shape is less likely to occur, and the transparency of the surface of the glass component 1 is less likely to be damaged.

[0075] Therefore, by setting the average value of the height of the apex of the convex portion on the surface of the glass member 1 to be within the above range, the water repellency of the surface of the glass member 1 can be further improved, and the transparency of the surface of the glass member 1 is less likely to be impaired.

[0076] In the present invention, when the cutoff value of the high-pass filter λc is set to 2.5 μm in a micro region of 5 μm×5 μm on the surface of the glass member 1, the skewness Ssk is preferably -0.10 or less, more preferably -0.20 or less, and even more preferably -0.30 or less. The skewness Ssk can be measured according to ISO 25178.

[0077] When the skewness Ssk of the surface of the glass component 1 is below the upper limit, the histogram of the height of the concavo-convex shape is distributed upward, the concave portion is deeper than the convex portion, and the concavo-convex shape is sharper. As a result, the air layer retained by the concave portion is not easily squeezed out by the liquid, and the air layer is more easily retained, thereby further improving the water repellency of the surface of the glass component 1.

[0078] In addition, the lower limit value of the skewness Ssk of the surface of the glass member 1 is not particularly limited, and may be -10, for example.

[0079] In the present invention, in a micro region of 5 μm×5 μm at a position lower than the reference surface, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the skewness SskA is preferably less than -0.10, more preferably less than -0.20, and further preferably less than -0.30. The skewness SskA can be measured in accordance with ISO 25178, similarly to the "skewness Ssk". Specifically, the skewness SskA is as follows: Figure 3 As shown by the dotted line A, it can be obtained by measuring the skewness of a small area lower than the above-mentioned reference surface.

[0080] When the skewness SskA of the surface of the glass member 1 is equal to or less than the above upper limit, it is easier to maintain the air layer, and the water repellency of the surface of the glass member 1 can be further improved.

[0081] In addition, the lower limit value of the skewness SskA of the surface of the glass member 1 is not particularly limited, and may be -10, for example.

[0082] In the present invention, in a micro area of ​​5 μm×5 μm at the top of a convex portion having a height of 50 nm or more from the reference surface, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the skewness SskB is preferably less than -0.10, more preferably less than -0.20, and further preferably less than -0.30. The skewness SskB can be measured in accordance with ISO25178 in the same manner as the "skewness Ssk". Specifically, the skewness SskB is as follows: Figure 3 As shown by the dotted line B, it can be obtained by measuring the skewness of a micro region at the top of a convex portion having a height of 50 nm or more from the above-mentioned reference plane.

[0083] When the skewness SskB of the surface of the glass member 1 is equal to or less than the above upper limit, it is easier to maintain the air layer, and the water repellency of the surface of the glass member 1 can be further improved.

[0084] In addition, the lower limit value of the skewness SskB of the surface of the glass member 1 is not particularly limited, and may be -10, for example.

[0085] In the present invention, the skewness Ssk may be any of the skewness SskA and the skewness SskB, or may be an average value of the skewness SskA and the skewness SskB.

[0086] In addition, when measuring the skewness SskA and the skewness SskB, if the measurement area cannot obtain a 5μm×5μm area (for example, when the area of ​​the convex portion is less than 5μm×5μm), or if the measurement area includes the boundary between the convex portion and the concave portion, the measured value is not used. In addition, when measuring the skewness Ssk, if either the skewness SskA or the skewness SskB cannot be measured, the measured value of the measurable one is used.

[0087] In this specification, the term "water repellency" means that the contact angle represented by the angle between the tangent line of the liquid surface and the solid surface, which includes the liquid side, is 90° or more.

[0088] Specifically, the contact angle between the surface of the glass component 1 and water is 90° or more, preferably 93° or more, more preferably 95° or more, further preferably 97° or more, and particularly preferably 100° or more. In this case, the water repellency of the surface of the glass component 1 can be further improved. The upper limit of the contact angle between the surface of the glass component 1 and water is not particularly limited, and can be, for example, 180°.

[0089] The contact angle (θ) of the surface of the glass member 1 can be measured based on the sessile drop method (θ / 2 approximation method) of JIS R 3257: 1999. For example, in the present embodiment, the contact angle (θ) can be measured by placing the glass member 1 horizontally with the first main surface 1a facing upward, dropping 2 μL of pure water, and photographing the water drop from the front side using a digital microscope (manufactured by Keyence, product name "VHX-500F").

[0090] In the present invention, the haze of the glass member 1 can be selected to any value according to the required characteristics and purpose. For example, in the case where it is necessary to more reliably ensure transparency, the haze of the glass member 1 is preferably less than 90%, more preferably 80% or less, further preferably 70% or less, further preferably 60% or less, further preferably 50% or less, further preferably 40% or less, further preferably 30% or less, further preferably 20% or less. On the other hand, from the viewpoint of more reliably suppressing reflection, the haze of the glass member 1 is preferably 3% or more, more preferably 5% or more, further preferably 10% or more, further preferably 15% or more, further preferably 20% or more, further preferably 25% or more, further preferably 30% or more, further preferably 35% or more.

[0091] The glass component 1 of this embodiment has excellent water repellency and can be applied to lens components and cover components of cameras used outdoors, such as vehicle-mounted cameras or surveillance cameras. In addition, the glass component 1 of this embodiment can also be applied to window panel components of automobiles, railway vehicles, ships, and aircraft.

[0092] (Manufacturing method)

[0093] Next, an example of a method for manufacturing the glass member 1 will be described.

[0094] The irregularities on the first main surface 1 a of the glass member 1 are formed by subjecting the surface of the original glass member to chemical etching and then to wet sandblasting.

[0095] Chemical etching is a process for forming projections and depressions by immersing the original glass member in an etching solution such as hydrofluoric acid. The number (N) and value (S / N) of projections on the surface of the obtained glass member 1 can be adjusted by chemical etching.

[0096] In the chemical etching process, the composition of the etching solution may be, for example, a mixed solution containing hydrofluoric acid and ammonium fluoride, a mixed solution containing hydrofluoric acid and potassium hydrogen fluoride, or a mixed solution containing hydrofluoric acid and sodium hydrogen fluoride. The etching solution may also contain other acids such as sulfuric acid, nitric acid, and hydrochloric acid, and chelating agents such as citric acid or ethylenediaminetetraacetic acid.

[0097] The content of hydrofluoric acid in the etching solution may be, for example, 0.1% by mass or more and 50% by mass or less. The content of ammonium fluoride in the etching solution may be, for example, 1% by mass or more and 40% by mass or less. The content of potassium hydrogen fluoride in the etching solution may be, for example, 1% by mass or more and 40% by mass or less. The content of sodium hydrogen fluoride in the etching solution may be, for example, 1% by mass or more and 40% by mass or less. In addition, the content of water in the etching solution may be, for example, 10% by mass or more and 98.9% by mass or less.

[0098] The processing temperature of the chemical etching treatment may be, for example, not less than 10° C. and not more than 50° C. In addition, the processing time of the chemical etching treatment may be, for example, not less than 1 second and not more than 3 hours.

[0099] The number (N) or value (S / N) of the protrusions can be adjusted according to the etching solution composition, processing time, processing temperature, etc. of the chemical etching process. That is, the number (N) of the protrusions can be increased by increasing the content of ammonium fluoride, potassium hydrogen fluoride, or sodium hydrogen fluoride in the etching solution or by increasing the processing temperature using the etching solution.

[0100] Specifically, by increasing the content of ammonium fluoride, potassium bifluoride or sodium bifluoride in the etching solution, or by increasing the processing temperature of the etching solution, when performing etching treatment at the same depth, there is a tendency that the number of protrusions (N) formed by etching increases, and the projected area (S) outside the protrusions decreases (the area of ​​the protrusions increases). When the projected area (S) outside the protrusions further decreases (the area of ​​the protrusions further increases), there is a tendency that the number of protrusions (N) decreases due to adjacent protrusions sticking together. In addition, when the content of hydrofluoric acid in the etching solution increases, or when only the etching processing time is prolonged, the area of ​​the protrusions formed by etching increases, and the projected area (S) outside the protrusions decreases. The number of protrusions (N) and the projected area (S) outside the protrusions are determined by the balance of these processing conditions.

[0101] Wet blasting is a process in which a slurry made of abrasive particles such as aluminum oxide and a liquid such as water is uniformly mixed and sprayed from a nozzle at high speed onto a workpiece made of a raw glass component using compressed air, thereby forming fine irregularities on the workpiece.

[0102] In wet blasting, when the slurry ejected at high speed collides with the workpiece, the abrasive grains in the slurry grind, collide or rub against the surface of the workpiece, thereby forming fine irregularities on the surface of the workpiece.

[0103] In this case, the abrasive grains ejected onto the workpiece and the fragments of the workpiece cut off by the abrasive grains are washed away by the liquid ejected onto the workpiece, so that the number of particles remaining on the workpiece decreases.

[0104] In wet blasting, when slurry is sprayed onto a workpiece, abrasive grains are brought to the workpiece by liquid, so fine abrasive grains can be used more easily than in dry blasting, and the impact when the abrasive grains collide with the workpiece is reduced, enabling precise processing.

[0105] In wet sandblasting, the average particle size of the abrasive grains can be, for example, 0.2 μm or more and 60 μm or less. The air pressure when spraying the slurry containing the abrasive grains can be, for example, 0.1 MPa or more and 0.5 MPa or less. In addition, the scanning speed of the nozzle can be, for example, 0.1 mm / s or more and 100 mm / s or less. The average particle size of the abrasive grains can be measured, for example, by a resistance method.

[0106] Furthermore, the arithmetic mean height Sa of the surface of the glass member 1 can be increased by increasing the average particle size of abrasive grains in the wet blasting process, increasing the ejection pressure of the slurry, or decreasing the scanning speed of the nozzle.

[0107] Alternatively, before the chemical etching process, the original glass member may be subjected to a first wet blasting process to provide the original glass member with irregularities that serve as etching starting points, and after the chemical etching process, a second wet blasting process may be performed.

[0108] Thus, by subjecting the workpiece (original glass member) to chemical etching and wet blasting, a concavo-convex shape of appropriate size can be formed on the surface of the glass member 1. Thus, the water repellency of the surface of the glass member 1 can be improved without impairing the transparency of the glass member 1.

[0109] (Second Embodiment)

[0110] Figure 4 2 is a schematic cross-sectional view showing a glass component according to a second embodiment of the present invention. Figure 4 As shown, the glass member 21 includes a glass member main body 22 and a functional film 23. The functional film 23 is provided on a principal surface 22a of the glass member main body 22.

[0111] In this embodiment, the same concavoconvexity as the first main surface 1a of the glass component 1 of the first embodiment is formed on the main surface 21a of the glass component 21 (the main surface of the functional film 23). In this way, when the functional film 23 is formed on the main surface 22a of the glass component body 22, it is sufficient to form the concavoconvex shape on the main surface 22a of the glass component body 22 in advance so that the concavoconvex shape of the main surface (main surface 21a) of the functional film 23 after formation becomes the same concavoconvex shape as the main surface 1a of the glass component 1 of the first embodiment. In addition, the concavoconvexity may be formed after the functional film 23 is formed. In this case, the functional film 23 is preferably formed into a film thicker than the concavoconvex shape to be formed.

[0112] As the functional film 23, for example, a water-repellent film can be used. In addition, in this embodiment, the same concavo-convex as the first main surface 1a of the glass member 1 of the first embodiment is formed on the main surface 21a of the glass member 21 (the main surface of the functional film 23), so even if the water-repellent film is worn or peeled off due to friction such as friction, the above-mentioned concavo-convex can also impart high water repellency. Therefore, the high water repellency can be maintained for a long time.

[0113] As the water-repellent film, an organic film for improving water repellency can be used. As the organic film, a compound having a fluorine-modified organic group and a silyl group, a silane compound containing an alkyl group or a fluoroalkyl group, etc. can be used. Specifically, the organic film can be formed (film-formed) by combining a silane compound containing an alkyl group or a fluoroalkyl group with the surface of the glass component body 22. In addition, the water-repellent film can also contain a silicone resin, wherein it can also be an organic film containing a methyl silicone resin, a methylphenyl silicone resin, an alkyd-modified silicone resin, an epoxy-modified silicone resin, an acrylic-modified silicone resin, a polyester-modified silicone resin, a fluorine-modified silicone resin, etc.

[0114] In addition, the functional film 23 may also be an optical functional film. As the optical functional film, for example, an anti-reflection film or a reflective film may be used. As the anti-reflection film and the reflective film, a low-refractive index film having a lower refractive index than the glass component body 22, or a dielectric multilayer film formed by alternately stacking a low-refractive index film having a relatively low refractive index and a high-refractive index film having a relatively high refractive index may be used. The anti-reflection film and the reflective film may be formed by a sputtering method or a CVD method, etc.

[0115] The thickness of the functional film 23 is not particularly limited unless the effects of the present invention are impaired, and may be, for example, 1 nm to 5 μm.

[0116] Other aspects are the same as those of the first embodiment.

[0117] The glass member 21 of this embodiment also has the above-mentioned structure of the present invention and therefore has excellent water repellency.

[0118] Hereinafter, the present invention will be described in more detail based on specific examples. The present invention is not limited to the following examples at all, and can be implemented with appropriate modifications within the scope of the present invention.

[0119] (Examples 1 to 10)

[0120] In Examples 1 to 10, first, a 0.5 mm thick aluminosilicate glass having a rectangular plate shape (manufactured by Nippon Electric Glass Co., Ltd., product name “T2X-1”) was prepared.

[0121] Next, the entire main surface of one side of the prepared aluminosilicate glass (hereinafter referred to as glass) is chemically etched. Next, the entire main surface of one side of the chemically etched glass is wet blasted to produce a glass component.

[0122] In the chemical etching treatment, the glass is immersed in an etching solution prepared to have a hydrofluoric acid content of 1.6 mass % to 6.0 mass %, ammonium fluoride of 20.0 mass % to 38.7 mass % and water of 59.7 mass % to 75.0 mass %, at a liquid temperature of 20° C. to 40° C. and a treatment time of 0.5 minute to 10 minutes to perform chemical etching.

[0123] In the wet sandblasting treatment, first, abrasive grains composed of aluminum oxide with an average particle size of 1.2 μm to 2.0 μm are uniformly stirred with water to prepare a slurry. Then, the wet sandblasting treatment is performed by spraying the prepared slurry onto the entire main surface of the one side of each glass. The slurry is sprayed by moving the nozzle at a scanning speed of 10 mm / s while scanning and spraying the prepared slurry from the nozzle at an air pressure of 0.1 MPa to 0.3 MPa.

[0124] According to the above operation, a glass member having unevenness on the surface was produced. The production conditions of the glass members of Examples 1 to 10 are shown in Tables 1 and 2 below.

[0125] [Table 1]

[0126]

[0127] [Table 2]

[0128]

[0129] (Comparative Example 1)

[0130] In Comparative Example 1, chemical etching was performed in the same manner as in Example 3, but wet blasting was not performed. In other respects, the same procedures were followed as in Example 3 to obtain a glass member (Table 2).

[0131] (Comparative Example 2)

[0132] In Comparative Example 2, a glass member was produced by subjecting the entire main surface of one side of the glass to only wet blasting in the same manner as in Example 1. Therefore, in Comparative Example 2, chemical etching was not performed (Table 2).

[0133] In the wet blasting process, first, abrasive grains composed of aluminum oxide with an average particle size of 1.2 μm were uniformly stirred with water to prepare a slurry. Then, the wet blasting process was performed by spraying the prepared slurry onto the entire main surface of one side of the glass. The slurry was sprayed by moving the nozzle at a scanning speed of 10 mm / s while scanning and spraying the prepared slurry from the nozzle at an air pressure of 0.2 MPa.

[0134] (Comparative Example 3)

[0135] In Comparative Example 3, the same aluminosilicate glass as that in Example 1 was used as it is without being subjected to any treatment.

[0136] (Comparative Example 4)

[0137] In Comparative Example 4, the chemical etching process was performed by changing the composition of the etching solution used in the chemical etching process and the chemical etching process conditions as shown in Table 2. Therefore, in Comparative Example 4, the wet blasting process was not performed.

[0138] (evaluate)

[0139] [Measurement of surface shape]

[0140] (Measurement of convex portion)

[0141] The surface roughness of the main surfaces of the glass members of Examples 1 to 10 and Comparative Examples 1 to 4 was measured based on ISO 25178. The surface roughness was measured on each main surface having projections and depressions formed thereon. These were measured using a laser microscope (Keyence, product number "VK-X250").

[0142] The measurement conditions of Examples 1 to 10 and Comparative Examples 1 to 4 were implemented by using an objective lens of 150 times, and obtaining data of 2048 × 1536 for a measurement area of ​​96 μm × 72 μm. After removing the tilt of the plane using the least squares method, the threshold of the height cutoff level was set to 50 to remove the noise in the height direction, and the analysis was performed.

[0143] Number of convex parts (N):

[0144] For the data of the measurement area of ​​96μm×72μm, the average plane of the average height of the concave and convex in the Z direction was used as the reference plane, and the height from the average value + 50nm was used as the threshold for binarization, and the independent area with a height above the threshold was regarded as a convex part. The horizontal cross-sectional area at the threshold is 0.2μm 2 The following areas are excluded. In addition, the number of convex portions (N) is calculated from the number of independent areas with a height above the threshold value when binarization is performed using the threshold value. The horizontal cross-sectional area of ​​the threshold value is 0.2 μm2 The following convex parts are excluded. In addition, when the arithmetic mean height of the measurement area is less than 5.0nm, it is regarded as a smooth surface without concavities and convexities, and the number of convex parts is set to 0. Similarly, the height from the average value + 100nm is used as a threshold for binarization to obtain the number of convex parts (N2).

[0145] Increase / decrease rate ((|N-N2| / N)×100):

[0146] It is determined by dividing the absolute value of the difference between the number of convex portions (N) and the number of convex portions (N2) by the number of convex portions (N).

[0147] Value(S / N):

[0148] The value (S / N) is obtained by dividing the area (S) of the height less than 50nm from the reference plane by the number (N) of the convex parts having a height of 50nm or more from the reference plane when the average surface of the concave and convex parts is used as the reference plane in the measurement area of ​​96μm×72μm. The area (S) of the height less than 50nm from the reference plane refers to the area other than the area of ​​the convex parts, and is obtained as follows: the area of ​​the convex part is obtained by subtracting the area of ​​the convex part from the total projected area of ​​the area above the threshold value when the height of 50nm from the reference plane is used as the threshold value for binarization, and then the area of ​​the convex part is obtained.

[0149] Average height of convex part:

[0150] For all protrusions in the measurement area of ​​96μm×72μm with a height of more than 50nm from the above-mentioned reference plane, the maximum height from the above-mentioned reference plane (height 0.0μm), that is, the height of the apex of the protrusion, is calculated, and the average height of the apex height of the protrusion (average height of the protrusion) is calculated using the average value.

[0151] (arithmetic mean height and skewness)

[0152] On the main surfaces of the glass parts of Examples 1 to 10 and Comparative Examples 1 to 4, the surface roughness parameters (arithmetic mean height Sa and skewness Ssk) of the micro-areas are measured. Among them, in this measurement, as the arithmetic mean height Sa, the arithmetic mean height SaA of the micro-areas at the parts lower than the reference plane is measured, and as the skewness Ssk, the skewness SskA of the micro-areas at the parts lower than the reference plane is measured. The measurement of the surface roughness parameters is carried out on each main surface formed with concave and convex. In addition, similarly, the arithmetic mean height SaB and skewness SskB of the micro-areas at the top of the convex part with a height of more than 50nm from the reference plane are measured. These measurements are measured using an atomic force microscope (AFM).

[0153] Here, an atomic force microscope (manufactured by Bruker Corporation, trade name: Dimension Icon (SPM unit), NanoScope V (Controller unit)) was used as an atomic force microscope (AFM), and measurement was performed in accordance with ISO25178.

[0154] The measurement conditions were a tapping mode, a scanning rate of 1 Hz, and a number of acquired data of 512 x 512 for a micro-region of 5 μm x 5 μm, and analysis was performed with the cutoff value of the high-pass filter λc set to 2.5 μm.

[0155] [Measurement of contact angle θ]

[0156] The contact angle θ between the main surface of the glass members of Examples 1 to 10 and the glass members of Comparative Examples 1 to 4 and water was measured.

[0157] The contact angle θ was measured based on the sessile drop method (θ / 2 approximation method) of JIS R3257: 1999. Specifically, 2 μL of pure water was dropped onto each horizontally placed glass member with the main surface formed with the concavoconvex facing upward, and the water drop was photographed from the front side using a digital microscope (manufactured by Keyence, product name "VHX-500F") to measure the contact angle θ.

[0158] in, Figure 5 This is a photograph of a glass member obtained in Example 2 with water drops placed on its surface. Figure 6 This is a photograph showing a water drop placed on the surface of the glass member obtained in Comparative Example 1. Figure 7 This is a photograph of a glass member obtained in Comparative Example 2 when a water droplet is placed on the surface of the glass member.

[0159] like Figure 5 As shown in FIG. 2 , it can be seen that the glass member obtained in Example 2 has high water repellency (contact angle θ: 120°). Figure 6 and Figure 7 As shown, the water repellency of the glass members obtained in Comparative Examples 1 and 2 was insufficient (contact angle θ of Comparative Example 1: 47°, contact angle θ of Comparative Example 2: 80°).

[0160] [Measurement of haze]

[0161] Next, the haze of the glass members of Examples 1 to 10 and Comparative Examples 1 to 4 was measured. The haze was measured using an ultraviolet-visible-near-infrared spectrophotometer (UV-670) manufactured by Shimadzu Corporation in accordance with JIS K7361-1-1997.

[0162] The results are shown in Tables 3 and 4 below.

[0163] [Table 3]

[0164]

[0165] [Table 4]

[0166]

[0167] As shown in Tables 3 and 4, in the glass members of Examples 1 to 10, the contact angle θ was 99° to 120°, and it was confirmed that the glass members were excellent in water repellency.

[0168] On the other hand, in the glass members of Comparative Examples 1 to 4, the contact angles were 3° to 80°, which was an unfavorable result showing hydrophilicity.

[0169] In addition, the number (N) of the protrusions in Examples 1 to 10 is in the range of 21 to 221.

[0170] The arithmetic mean height Sa of Examples 1 to 10 was within the range of 3.6 nm to 20.4 nm. It was also confirmed that the arithmetic mean height Sa tended to increase as the average particle size of the abrasive grains and the gas pressure in the wet blasting process increased.

[0171] On the other hand, the number (N) of the protrusions of Comparative Example 1, which was subjected to only chemical etching, was 60. In addition, the arithmetic mean height Sa of Comparative Example 1 was 0.4 nm. Therefore, in Comparative Example 1, the arithmetic mean height Sa was a smaller value than that of Examples 1 to 10.

[0172] In Comparative Example 2, which was subjected to only wet blasting, the number (N) of protrusions was 8, and the arithmetic mean height Sa was 10.6 nm. Therefore, in Comparative Example 2, the number (N) of protrusions was smaller than that in the example.

[0173] In addition, the number (N) of the convex portions of the untreated comparative example 3 is 0, and the arithmetic mean height Sa is 0.1 nm. Therefore, the number (N) of the convex portions and the arithmetic mean height Sa of the untreated comparative example 3 are both small values ​​compared with those of Examples 1 to 10.

[0174] In addition, the number of protrusions (N) in Comparative Example 4 in which the composition of the chemical etching solution was changed was 2692. Therefore, in Comparative Example 4, the number of protrusions (N) was a value considerably large compared to Examples 1 to 10.

[0175] The values ​​(S / N) of Examples 1 to 10 are 26.7 μm 2 ~238.4μm 2 within the range.

[0176] On the other hand, the value (S / N) of Comparative Example 2 in which only wet blasting was performed was 857.0 μm.2 , which is a larger value than that of Examples 1 to 10. In addition, the value (S / N) of Comparative Example 4 in which the chemical etching solution composition was changed was 1.7 μm 2 , which is a smaller value than that of Examples 1 to 10.

[0177] The average height of the protrusions in Examples 1 to 10 was within a range of 0.19 μm to 4.16 μm. It was confirmed that the average height of the protrusions tended to increase as the hydrofluoric acid content of the etching solution increased, the temperature of the chemical etching increased, or the processing time increased.

[0178] On the other hand, in Comparative Example 2 in which only wet blasting was performed, the average height of the convex portions was 0.10 μm, which was a smaller value than that of the Examples.

[0179] The skewness Ssk of Examples 1 to 10 is within the range of -0.40 to -1.60.

[0180] On the other hand, in Comparative Example 1 in which only the chemical etching process was performed and Comparative Example 3 in which no process was performed, the skewness Ssk was 0.03 and 0.01, respectively.

[0181] From the above, it was confirmed that the water repellency of the glass member can be improved by controlling the parameters related to the roughness curve of the surface of the glass member.

[0182] In particular, in the glass members of Examples 1 to 10 in which the number (N) of convex portions in a 96 μm×72 μm region is 10 to 250 and the arithmetic mean height Sa of a 5 μm×5 μm microregion is 1.0 nm to 50.0 nm, it can be confirmed that the water repellency of the surface is improved.

[0183] Explanation of symbols

[0184] 1, 21: glass component; 1a, 1b: first main surface, second main surface; 21a, 22a: main surface; 22: glass component body; 23: functional film.

Claims

1. A glass component, characterized in that: The glass member has irregularities on at least a portion of its surface. In a 96 μm×72 μm area of ​​the surface having the irregularities, when the average plane of the irregularities is taken as a reference plane, the number of convex portions having a height of 50 nm or more from the reference plane is 10 to 250. In a micro region of 5 μm×5 μm on the surface having the irregularities, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the arithmetic mean height Sa is not less than 1.0 nm and not more than 50.0 nm.

2. A glass component, characterized in that: The glass member has irregularities on at least a portion of its surface. In a 96 μm×72 μm area of ​​the surface having the concavoconvexities, when the average surface of the concavoconvexities is taken as a reference surface, the value S / N obtained by dividing the area S of a height less than 50 nm from the reference surface by the number N of convex portions having a height of 50 nm or more from the reference surface is 20.0 μm 2 Above 500.0μm 2 the following, In a micro region of 5 μm×5 μm on the surface having the irregularities, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the arithmetic mean height Sa is not less than 1.0 nm and not more than 50.0 nm.

3. The glass component according to claim 1 or 2, characterized in that: In a 96 μm×72 μm region of the surface having the projections and recesses, an average value of the heights of the apexes of the projections from the reference plane is 0.10 μm or more and 5.00 μm or less.

4. The glass component according to claim 1 or 2, characterized in that: In a micro region of 5 μm×5 μm on the surface having the above-mentioned irregularities, when the cutoff value of the high-pass filter λc is set to 2.5 μm, the skewness Ssk is not more than −0.

10.

5. The glass component according to claim 1 or 2, characterized in that: The contact angle between the surface of the glass member having the projections and depressions and water is 90° or more.

6. The glass component according to claim 1 or 2, characterized in that: have: a glass component body; and A water-repellent film is provided on a main surface of the glass member body.

7. The glass component according to claim 1 or 2, characterized in that: have: a glass component body; and An optically functional film is provided on a main surface of the glass member body.

8. The glass component according to claim 7, characterized in that: The optical functional film is an anti-reflection film or a reflective film.

Citation Information

Patent Citations

  • Water-repellent cleaning structure for front lens at vehicle lighting fixture

    JP1994330363A